Association between sitagliptin use and heart failure hospitalization and related outcomes in type 2 diabetes mellitus: secondary analysis of a randomized clinical trial - McGuire, D; Van De Werf, F; Armstrong, P; Standl, E; Koglin, J; Green, J; Bethel, M; Cornel, J; Lopes, R; Halvorsen, S; Ambrosio, G; Buse, J; et al. (American Medical Association, 2016)
Importance Previous trial results have suggested that dipeptidyl peptidase 4 inhibitor (DPP4i) use might increase heart failure (HF) risk in type 2 diabetes mellitus (T2DM). The DPP4i sitagliptin has been shown to be noninferior to placebo with regard to primary and secondary composite atherosclerotic cardiovascular (CV) outcomes in the Trial Evaluating Cardiovascular Outcomes With Sitagliptin (TECOS). Objective To assess the association of sitagliptin use with hospitalization for HF (hHF) and related outcomes. Design, Setting, and Participants TECOS was a randomized, double-blind, placebo-controlled study evaluating the CV safety of sitagliptin vs placebo, each added to usual antihyperglycemic therapy and CV care among patients with T2DM and prevalent atherosclerotic vascular disease. The median follow-up was 2.9 years. The setting was 673 sites in 38 countries. Participants included 14 671 patients with T2DM and atherosclerotic vascular disease. The study dates were December 2008 through March 2015. Interventions Patients were randomized to sitagliptin vs placebo added to standard care. Main Outcomes and Measures Prespecified secondary analyses compared the effect on hHF, hHF or CV death, and hHF or all-cause death composite outcomes overall and in prespecified subgroups. Supportive analyses included total hHF events (first plus recurrent) and post-hHF death. Meta-analyses evaluated DPP4i effects on hHF and on hHF or CV death. Results Of 14 671 patients, 7332 were randomized to sitagliptin and 7339 to placebo. Hospitalization for HF occurred in 3.1% (n = 228) and 3.1% (n = 229) of the sitagliptin and placebo groups, respectively (unadjusted hazard ratio, 1.00; 95% CI, 0.83-1.19). There was also no difference in total hHF events between the sitagliptin (n = 345) and placebo (n = 347) groups (unadjusted hazard ratio, 1.00; 95% CI, 0.80-1.25). Post-hHF all-cause death was similar in the sitagliptin and placebo groups (29.8% vs 28.8%, respectively), as was CV death (22.4% vs 23.1%, respectively). No heterogeneity for the effect of sitagliptin on hHF was observed in subgroup analyses across 21 factors (P > .10 for all interactions). Meta-analysis of the hHF results from the 3 reported DPP4i CV outcomes trials revealed moderate heterogeneity (I2 = 44.9, P = .16). Conclusions and Relevance Sitagliptin use does not affect the risk for hHF in T2DM, both overall and among high-risk patient subgroups.